The End of Genre Curations and Experiments in Intentional Discourses - Faber, Brenton (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores early new critical debates about intention, tracing how and why intention was dismissed across much humanities scholarship, and how it can be revisited and made relevant as a key formative, evaluative, and ethical concept. The author argues that the academic disinterest in intention occurred simultaneously as genre criticism and later the rhetorical interest in genre came into its own. Genre became a way to simultaneously elide and naturalize intention. The book elaborates on the pedagogical, ethical, and empirical consequences naturalizing intention through genre has had for rhetorical studies and it offers a new term, "curations" to identify discursive forms, actions, and intentions working simultaneously. Finally, he also examines the gap between the humanities and STEM fields and shows specific ways scientists and engineers have called for the humanities to become more invested in intention as both a critical and an operational concept. This book will be of interest to students and scholars of discourse studies and critical discourse analysis, rhetoric and professional communication, including those in fields such as medicine, engineering, STS and business studies. .
Preface: From Interpretation to Production -- Chapter 1. Intentions: An Autobiography -- Chapter 2. After Intention -- Chapter 3. Nanotechnology and the City: Spacemaking, Utopia, Urban Myth -- Chapter 4. Medicine, Intention, Terministic Screens -- Chapter 5. Heuristics & Hermeneutics in Data Science: Analytics through the Lens of Intentionality -- Chapter 6. Curations form + action + intention -- Postscript.
Keywords: Knowledge, Sociology of; Literary form; Film genres; Professional education; Vocational education; Language and languages-Style.; Rhetoric; Sociology of Knowledge and Discourse; Literary Genre; Genre Studies; Professional and Vocational Education; Rhetorics